Frequencies of borderline pulmonary hypertension before and after the DETECT algorithm: results from a prospective systemic sclerosis cohort. (11th December 2017) - Hoffmann-Vold, Anna-Maria; Fretheim, Håvard; Midtvedt, Øyvind; Kilian, Karin; Angelshaug, Marianne; Chaudhary, Asad; Gunnarsson, Ragnar; Brunborg, Cathrine; Garen, Torhild; Andreassen, Arne K; Gude, Einar; Molberg, Øyvind
Abstract: Objective: The DETECT algorithm was developed for screening patients with SSc at high risk of pulmonary arterial hypertension (PAH). We evaluated the impact of this algorithm in a SSc population. Methods: Patients from the unselected, prospective Oslo University Hospital SSc study were divided into the Early and DETECT cohorts, respectively, depending on whether an incident right heart catheterization (RHC) was performed before (2009–13) or after (2014–17) the DETECT algorithm was instituted. A PAH diagnosis and patient risk stratification (low, intermediate and high risk) were performed according to 2015 European Society of Cardiology guidelines. Results: At the time of the incident RHC, PAH frequency was similar between the DETECT (15/84 with PAH; 18%) and Early (16/77; 21%) cohorts, but more patients had borderline pulmonary hypertension (PH) in the DETECT (31%) than in the Early (17%) cohort. PAH risk levels were distributed differently. In the DETECT cohort, 27% and 27% were at low and high risk, respectively, at the time of PAH diagnosis. In the Early cohort, 19 and 44% were at low and high risk, respectively. A follow-up RHC, performed after [mean (SD)] 2.4 (1.8) years, showed that 39% of patients with borderline PH in the Early cohort had developed PAH. Conclusion: The DETECT algorithm did not alter PAH incidence in this unselected SSc population. However, it appeared to affect the risk distribution at the time of PAH diagnosis and increased the frequency of borderline PH cases. These findings may translate into novel opportunities for earlier PAH treatment and, possibly, prevention.